’’ قتل غیرت‘‘ اسلامی تعلیمات سے متصادم رویہ ایک تجزیاتی مطالعہ: "Honor Killing" An Attitude in Conflict with Islamic Teaching An Analytical Study - Shehzadi, Saima; Haseeb, Ahmed (Al-Irfan, 2024)
Among the major problems faced by women in Pakistan is honor killing. This problem is being carried on from generation to generation on cultural basis. To cover up the man's passion killing, it is saved by giving it the color of honor killing and the women treated like a meaningless creature. While this violent act has never been encouraged in Pakistani personal law. The majority population of Pakistan claims to be followers of the religion of Islam, whose basic teachings are the source of peace and security of humanity. Despite this, every year countless men and women are victims of this cruel bloodshed, in which the overwhelming majority are women. Ironically, to justify such accrued act and escape to punishment it is linked to Qur’anic teachings, which is totally misleading. In this conference paper, will explained the legality of honor killing by presenting it in the context of Islamic teachings.